Inequalities in access to biological treatments for psoriasis: results from the Italian Psocare registry. (5th April 2017) - Naldi, L.; Cazzaniga, S.; Di Mercurio, M.; Grossi, E.; Addis, A.; ,
Summary: Background: Limited evidence is available on the impact of socioeconomic factors on drug prescriptions for psoriasis. Objectives: To investigate factors influencing prescription of conventional vs. biological treatment for patients with psoriasis, based on the Italian Psocare registry, with a special focus on socioeconomic factors. Methods: This was a cross‐sectional study evaluating the baseline data of patients included in the Psocare registry. All of the consecutive adult patients with a diagnosis of chronic plaque psoriasis or psoriatic arthritis who were prescribed a systemic treatment for psoriasis at participating centres were included in this study. Univariate and multivariate analyses of the baseline factors associated with a biologics prescription were performed. Results: From September 2005 to September 2009, 12 838 patients were identified. A multivariate analysis revealed that, among other factors, completing a level of education higher than lower secondary school and being employed as a manager or a professional were independent factors associated with a biologics prescription at entry in the registry. Additional analyses on the association between these two variables and a severe psoriasis condition [Psoriasis Area Severity Index (PASI) score > 20] revealed a significantly increasing trend of severe disease towards lower educational attainment, while unemployed patients were more likely to have a more severe condition compared with the other categories of workers. Conclusions: We documented inequalities of drug prescriptions for psoriasis in Italy, with a trend towards a higher frequency of prescription for more expensive biologics in higher socioeconomic sectors of the population. Abstract : What's already known about this topic? Disparities in healthcare provisions and outcomes have been noted in several medical areas but little is known about these disparities in dermatology. Data from Medicare in the U.S.A. indicated financial and racial barriers to receipt of biological therapies in psoriasis. What does this study add? We documented inequalities of drug prescriptions for psoriasis in Italy, with a trend towards a higher frequency of prescription for more expensive biologics in higher socioeconomic sectors of the population. Respond to this article